Best Input Factors in EDM 90CrSi Using Graphite Electrodes by TOPSIS Method - Le, Thi Phuong Thao; Nguyen, Thi Quoc Dung; Vu, Trung Tuyen (European Journal of Applied Sciences, 2024)
This research presents a study that found the ideal process variables for Electrical Discharge Machining (EDM) of 90CrSi using graphite electrodes. This work used a multi-criteria decision making (MCDM) approach for the first time to produce cylindrical-shaped parts utilizing the EDM technique and various kinds of graphite as the electrode material. The MCDM problem was solved using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) approach, and the weights of the criteria were estimated using the Entropy method. Furthermore, the two investigational criteria used were electrode wear rate (EWR) and material removal rate (MRR). Furthermore, five process factors were examined: servo voltage (SV), servo current (IP), pulse on time (Ton), pulse off time (Toff), and graphite type (TOG). In addition, the experiment was designed and the outcomes were assessed using the Taguchi method in Minitab R19 software. Furthermore, for this experiment, the design L18 (6^1 + 3^4) was used. The MCDM issue has been resolved, and the ideal process parameters were recommended.